Engagement with Social and Digital Platforms for Language Teaching Competencies among Language Pre-Service Teachers - Oyetoro, Oyebode Stephen; Oluajo, Damilola Abiodun (Universitas Jambi, Magister Program of English Education Department, 2025)
This study investigated the engagement of language preservice teachers at Obafemi Awolowo University (OAU) with social and digital platforms in acquiring language-teaching competencies. A survey design was employed using a researcher-designed questionnaire administered to 213 penultimate and final-year preservice teachers in Yoruba, French, and Education/English programmes during the 2023/2024 academic session. Descriptive statistics, including frequency counts and percentages, were used for analysis, with visualisation tools such as bar and pie charts. Findings showed that YouTube (21.33%) and Facebook Groups (15.54%) were the most frequently used platforms. A total of 182 respondents (86.26%) affirmed that these platforms enhance and effectively develop language teaching competencies, particularly lesson Planning (71.56%), as well as technology integration, classroom management, and proficiency development (17.06%–19.91%). Significant challenges included limited internet access (29.32%), lack of reliable resources and exposure to misinformation (8.53%), and time constraints (7.11%). The study concludes that social and digital platforms significantly contribute to preparing preservice teachers for contemporary language teaching demands. It highlights the need to address access and reliability challenges to optimize their instructional benefits.